ADSORPSI KATION Pb (II) PADA LEMPUNG CENGAR TERAKTIVASI ASAM SULFAT : PENGARUH WAKTU KONTAK - Rama Anggun Sari; Muhdarina '; Nurhayati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The adsorption ability of activated sulfuric acid Cengar clays (LC0.2, LC0.4 and LC0.6) has been studied using cation of Pb (II) in aqueous solution. The adsorption experiments were observed at each contact time i.e 5, 15, 30, 60, 70, 80, 90 and 120 minutes. All of the experiments were done at a temperature of 30°C and initial concentration of 20 ppm. The amount of Pb (II) adsorbed by the adsorbents was measured by Atomic Absorption Spectrophotometer (AAS). All data was then applied into kinetic models of the pseudofirst order, pseudo-second order and Elovich to determine the adsorption behavior. We found that 0.759, 0.799 and 0.827 mg g-1 Pb were adsorbed by LC0.2, LC0.4 and LC0.6 at 90 minutes contact time, respectively. All of the activated sulfuric acid Cengar clays which adsorbed Pb (II) cations according to pseudo second-order kinetics with  k values (g mg -1 min -1 ) of each adsorbent were 0.156, 0.228 and 0.311, respectively. Fulfillment of the pseudo second-order models has indicated that the process occured was chemicaladsorption.